2018
DOI: 10.12788/ajo.2018.0049
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Peripheral Nerve Block in Hip Arthroscopy

Abstract: Pain control following hip arthroscopy presents a significant clinical challenge, with postoperative pain requiring considerable opioid use. Peripheral nerve blocks (PNBs) have emerged as one option to improve pain and limit the consequences of opioid use. The purpose of this study is to provide a comprehensive review of outcomes associated with PNB in hip arthroscopy. We hypothesize that the use of PNB in hip arthroscopy leads to improved outcomes and is associated with few complications. A systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Cannulated screw fixation is usually required for older children in whom transcervical fracture is unstable, and the determination of open versus closed approach commonly depends on the success of surgical traction for reduction. Regional anesthetic techniques are safe in children [ 14 16 ] and can provide analgesia for pediatric patients undergoing hip surgery [ 3 6 ]. Adequate analgesia results in faster rehabilitation, decreased opioid consumption, and avoidance of the untoward side effects associated with opioids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannulated screw fixation is usually required for older children in whom transcervical fracture is unstable, and the determination of open versus closed approach commonly depends on the success of surgical traction for reduction. Regional anesthetic techniques are safe in children [ 14 16 ] and can provide analgesia for pediatric patients undergoing hip surgery [ 3 6 ]. Adequate analgesia results in faster rehabilitation, decreased opioid consumption, and avoidance of the untoward side effects associated with opioids.…”
Section: Discussionmentioning
confidence: 99%
“…As such, regional anesthesia is advantageous in providing sufficient analgesia while reducing the adverse effects of opioids. Lumbar plexus blockade, neuraxial techniques (caudal or epidural), and combined femoral nerve and fascia iliaca blockade have been shown in a myriad of pediatric studies to exhibit opioid-sparing effects and lower postoperative pain scores in patients who are suffering from hip pain [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When evaluating hip arthroscopy, peripheral nerve blocks have been proven to be an effective method of analgesia with a relatively low complication rate. 3 , 9 , 10 , 11 , 12 , 13 Dold et al. 21 have reported that femoral nerve blocks were found to be more effective than general anesthesia alone with standard pain medications at reducing pain levels 60 minutes postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Generally, regional nerve blocks have proven effective in hip arthroscopy and are commonly employed as part of a multimodal pain control plan. 9 , 10 , 11 , 12 , 13 As the prevalence of hip arthroscopy has increased in recent years, so has the search for the most effective and safest technique for postoperative analgesia in these patients.…”
mentioning
confidence: 99%